Problems of Students in Learning Arabic Language at Madrasah Aliyah - Qomari, Vikri Aflaha; Kaputra, Soni; Namira, Silva; Febriani, Afifah; Nasution, Abdul Rahim; Arifin, Zainul (International Journal of Multidisciplinary Research of Higher Education, 2022)
Arabic is one of the subjects studied at the State Aliyah Madrasah. However, Arabic is only taught in a limited number of hours, as a result, problems arise in learning Arabic where students find it difficult to understand learning Arabic. So, it is necessary to do a study to identify these problems. This research aims to identify the problems of learning Arabic in the Three Cities of Padang Madrasah Aliyah Negeri (MAN) of West Sumatra. This study used a qualitative method with the type of case study, data sources were taken from ten informants through direct interviews using a set of interview protocols. All data were analyzed thematically using NVivo 12 software. The research findings found six themes regarding students' problems in learning Arabic. The six themes are i) differences in educational background, ii) low vocabulary mastery, iii) lack of teacher initiative to develop an Arabic-language environment, iv) lack of language labs, v) less varied learning methods, and vi) unsupportive environment. The results of this study can be used as initial data for future researchers in studying this problem in different contexts.